Crowdsourcing, citizen science or volunteered geographic information? The current state of crowdsourced geographic information - See, Linda; Mooney, Peter; Foody, Giles M.; Bastin, Lucy; Comber, A.; Estima, Jacinto; Fritz, Steffen; Kerle, Norman; Jiang, Bin; Laakso, Mari; Liu, Hai-Ying; Milčinski, Grega; et al. (MDPI, 2016)
Citizens are increasingly becoming an important source of geographic information, sometimes entering domains that had until recently been the exclusive realm of authoritative agencies. This activity has a very diverse character as it can, amongst other things, be active or passive, involve spatial or aspatial data and the data provided can be variable in terms of key attributes such as format, description and quality. Unsurprisingly, therefore, there are a variety of terms used to describe data arising from citizens. In this article, the expressions used to describe citizen sensing of geographic information are reviewed and their use over time explored, prior to categorizing them and highlighting key issues in the current state of the subject. The latter involved a review of ~100 Internet sites with particular focus on their thematic topic, the nature of the data and issues such as incentives for contributors. This review suggests that most sites involve active rather than passive contribution, with citizens typically motivated by the desire to aid a worthy cause, often receiving little training. As such, this article provides a snapshot of the role of citizens in crowdsourcing geographic information and a guide to the current status of this rapidly emerging and evolving subject.